Infectivity and RNA Persistence of a Norovirus Surrogate, the Tulane Virus, in Oysters - Polo, David; Schaeffer, Julien; Teunis, Peter; Buchet, Vincent; Le Guyader, Françoise S. (Frontiers in Microbiology, 2018)
Oysters, being filter feeders, can accumulate some human pathogens such as norovirus, a highly infectious calicivirus, most common cause of acute gastroenteritis worldwide. Accumulated virus decays over a period of days to weeks, possibly rendering contaminated oysters safe again. Sensitive molecular methods have been set up for shellfish analysis but without answering the question of infectious virus detection. Using the Tulane virus, a norovirus surrogate that recognizes the same ligand as human norovirus in oyster tissues, the genome and infectious virus decay rates were estimated using inverse linear regression in a Bayesian framework for genome copies. Infectivity decreased faster than genome copies but infectious viruses were detected for several days. Quantifying the decrease in viral infectivity and genome detection in oysters over such a long period may help local authorities to manage production areas implicated in shellfish-borne outbreaks, and thus protect consumers.